Transport at COP21 : Part of the Climate Change Solution - Ebinger, Jane; Peltier, Nicolas; Gitay, Habiba; Monsalve, Carolina; Losos, Andrew; Rogers, John Allen; Vandycke, Nancy (World Bank, Washington, DC, 2016)
The case for climate action has never been stronger. Around the world, climate change is putting at risk the lives of millions of people as well as threatening many coastal cities and endangering trillion of dollars of investments in transport infrastructure and services. The Twenty-First Conference of the Parties (COP21) to the United Nations Framework Convention on Climate Change (UNFCCC) will bring heads of state and ministers to Paris at the end of November to reach a global climate agreement with far-reaching implications for low-carbon and climate-resilient growth. Transport is playing a greater role in COP21 than in past UNFCCC conferences as a critical part of the solution: a sector that can contribute to both reducing greenhouse gas (GHG) emissions and building economy wide resilience to the impacts of climate change. In view of the sector’s potential, the heavily debated transport question is how to sustainably meet the rising global demand for greater interconnectedness and mobility. The World Bank and the seven other leading multilateral development banks have joined forces with the Paris Process for Mobility and Climate (PPMC) and the rest of the transport community to call for more action on transport and climate change.